Early Neanderthals in contact: The Chibanian (Middle Pleistocene) hominin dentition from Velika Balanica Cave, Southern Serbia. Issue 166 (May 2022) - Roksandic, Mirjana; Radović, Predrag; Lindal, Joshua; Mihailović, Dušan
Abstract: Neanderthals are Eurasian fossil hominins whose distinctive morphology developed in the southwestern corner of Europe and later spread throughout the continent, reaching Southwest Asia before the Late Pleistocene and spreading into Central Asia by 59–49 ka. The timing, tempo, and route of the Neanderthal movements eastward are poorly documented. The earliest probable evidence of Neanderthals in Asia comes from Karain E Cave (Anatolia, Turkey), dated to 250–200 ka. We present four Chibanian (Middle Pleistocene) hominin specimens, representing at least two individuals, from Velika Balanica Cave (Serbia): a permanent upper third molar (BH-2), a deciduous upper fourth premolar (BH-3) refitted to a poorly preserved maxillary fragment with the permanent first molar in the alveolus (BH-4), and a permanent upper central incisor (BH-5). We provide descriptions of the teeth, as well as a comparative analysis of the well-preserved M 1 (BH-4), including assessments of cusp angles, relative occlusal polygon area, relative cusp base areas, two- and three-dimensional enamel thickness, and taurodontism. Morphology of both the occlusal surface and the enamel dentine junction of the M 1 indicates that the maxillary fragment and associated dP 4 belonged to an early Neanderthal child. The heavily worn I 1 and M 3 are consistent with the Neanderthal morphology, although they are less distinct taxonomically. These Chibanian remains with provenance from layer 3a are constrained by two thermoluminescence dates: 285 ± 34 ka and 295 ± 74 ka. They represent the earliest current evidence of Neanderthal spread into the Eastern Mediterranean Area. We discuss these findings in light of recent direct evidence for cultural connections between Southwestern Asia and Southeast Europe in the Chibanian. Highlights: Four teeth from Velika Balanica, Serbia, represent at least one adult and one child. The morphology of the teeth is consistent with early Neanderthals. At 300 ka, they are the earliest dated evidence of the Neanderthals in the region. Associated artifacts are comparable to Near Eastern contemporaneous assemblages. W European and SW Asian populations interacted in the Balkans during the Chibanian.